Pseudo-differential operators analysis, applications and computations - Rodino, L. (Luigi).; Wong, M. W. 1951- (Man Wah).; Zhu, Hongmei; SpringerLink (Online service). (Basel Birkhäuser, 2011)
This volume consists of eighteen peer-reviewed papers related to lectures on pseudo-differential operators presented at the meeting of the ISAAC Group in Pseudo-Differential Operators (IGPDO) held at Imperial College London on July 13?18, 2009. Featured in this volume are the analysis, applications and computations of pseudo-differential operators in mathematics, physics and signal analysis. This volume is a useful complement to the volumes ?Advances in Pseudo-Differential Operators?, ?Pseudo-Differential Operators and Related Topics?, ?Modern Trends in Pseudo-Differential Operators?, ?New Developments in Pseudo-Differential Operators? and ?Pseudo-Differential Operators: Complex Analysis and Partial Differential Equations? published in the same series in, respectively, 2004, 2006, 2007, 2009 and 2010.
Preface -- Adaptive Wavelet Computations for Inverses of Pseudo-Differential Operators -- Spectral Theory of Pseudo-Differential Operators on S1 -- A Characterization of Compact Pseudo-Differential Operators on S1 -- Melin Operator with Asymptotics on Manifolds with Corners -- The Iterative Structure of the Corner Calculus -- Elliptic Equations and Boundary Value Problems in Non-Smooth Domains -- Calculus of Pseudo-Differential Operators and a Local Index of Dirac Operators -- Lp Bounds for a Class of Fractional Powers of Subelliptic Operators -- The Heat Kernel and Green Function of the Generalized Hermite Operator, and the Abstract Cauchy Problem for the Abstract Hermite Operator -- Local Exponential Estimates for h-Pseudo-Differential Operators with Operator-Valued Symbols -- Global Solvability in Functional Spaces for Smooth Nonsingular Vector Fields in the Plane -- Fuchsian Mild Microfunctions with Fractional Order and their Applications to Hyperbolic Equations -- The Continuity of Solutions with respect to a Parameter to Symmetric Hyperbolic Systems -- Generalized Gevrey Ultradistributions and their Microlocal Analysis -- Weyl Rule and Pseudo-Differential Operators for Arbitrary Operators -- Time-Frequency Characterization of Stochastic Differential Equations -- Wigner Representation Associated with Linear Transformations of the Time-Frequency Plane -- Some Remarks on Localization Operators.
Electronic reproduction.
Keywords: Pseudodifferential operators -- Congresses .; Electronic books